The First Global Refugee Forum - Stojanović, Bojan (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2020)
The Global Refugee Forum (GRF) was held for the first time on December 16-18, 2019 at the Palace of Nations, Geneva, Switzerland. The event was hosted by the Government of Switzerland and the UNHCR. The basis for holding a GRF was provided in the Global Compact on Refugees (GCR). The importance of maintaining the GRF is extremely high, especially given that, in addition to the representatives of the states, representatives of international organizations, civil society organizations, economic and non-economic entities, as well as refugee representatives participated in the GRF. In accordance with the obligations proclaimed by the New York Declaration, as well as the GCR, it is necessary to establish mechanisms for monitoring the fulfillment of these documents, as well as networks for cooperation of all factors that should contribute to the implementation of the GCR.
Keywords: refugees; Global Refugee Forum; Global Compact on Refugees